2022
DOI: 10.1002/slct.202104139
|View full text |Cite
|
Sign up to set email alerts
|

NiS Nanospheres Anchored onto a Graphene Oxide Substrate (NiS@GO) for Efficient Electrochemical Sensing of Trace Amounts of Silver Ions

Abstract: Electrochemical analysis is a promising method among all the common analytical technologies reported, due to its considerable sensitivity, inherent portability and low-cost requirements. To accurately monitor the contamination of heavy metal Ag + , NiS nanospheres anchored onto graphene oxide substrate (NiS@GO) were successfully constructed as a electrochemical sensor, by one-pot precipitation-co-self-assembly method. Under the optimized conditions, the obtained NiS@GO ex-hibited a synergistic electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20] However, these methods commonly suffer from disadvantages including the limited sensitivity, expensive equipment and complicated operating steps. 21,22 It has been reported that Ag + ions are able to selectively coordinate cytosine (C) bases and form a stable cytosine-Ag + -cytosine (C-Ag + -C) complex. 23 Various biosensors based on the interaction of the C-Ag + -C mismatch structure have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] However, these methods commonly suffer from disadvantages including the limited sensitivity, expensive equipment and complicated operating steps. 21,22 It has been reported that Ag + ions are able to selectively coordinate cytosine (C) bases and form a stable cytosine-Ag + -cytosine (C-Ag + -C) complex. 23 Various biosensors based on the interaction of the C-Ag + -C mismatch structure have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GO as a promising supporting material has been popularly used in electrochemical sensor field due to its large specific surface area, unique electronic properties and conductivity. [16][17][18][19] GO not only disperses and stabilizes inorganic nanoparticles but also provides fertile opportunities for the adsorption of molecules, which facilitates the construction of efficient sensors. Dopamine (DA) [20][21] is one of the familiar neurotransmitter that is used to transfer information in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse oxygen‐containing functional groups were linked to the carbon atoms, including carboxylic, hydroxyl and epoxide, which enhanced its solubility and stability. In addition, GO as a promising supporting material has been popularly used in electrochemical sensor field due to its large specific surface area, unique electronic properties and conductivity [16–19] . GO not only disperses and stabilizes inorganic nanoparticles but also provides fertile opportunities for the adsorption of molecules, which facilitates the construction of efficient sensors.…”
Section: Introductionmentioning
confidence: 99%